CASE REPORTSVeno-venous ECMO for carbon dioxide removal in a neonate after Norwood operation with an RV-PA shunt - Mroczek, Tomasz; Jarosz, Jerzy; Stycuła, Wojciech; Miklaszewska, Monika; Dudyńska, Miroława; Skalski, Janusz Hieronim (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
We describe a case of a newborn with a single-ventricle congenital heart defect, in which veno-venous extracorporeal membrane oxygenation (ECMO) was successfully employed shortly after a Norwood operation with right ventricle-to-pulmonary artery shunt due to pulmonary insufficiency.